The level of knowledge, attitudes and family skills in caring elderly in psychosocial function: Tingkat pengetahuan, sikap dan keterampilan keluarga dalam merawat fungsi psikososial Lansia - abdurrahman hamid; Agnita Utami (STIKes Hang Tuah Pekanbaru, 2019)
Abstract A healthy older adult life cannot be achieved alone by the older adult , but also requires the involvement of family members. Achieving optimal quality of life in the older adult must be supported by psychosocial care. Family members help the older adult meet their needs in achieving optimal quality of life. The purpose of this research is to help to provide an overview of family knowledge, attitudes and skills in caring for the psychosocial older adult . In this case the psychosocial function is memory, intellectual function, orientation of time and place. The sample in this study amounted to 30 families with a purposive sampling method. Data collection using the instrument in the form of a questionnaire and using the method of interviews and direct observation of families who have older adult family members. The results of the study revealed that the level of knowledge and skills was largely low, and family attitudes in caring for the older adult were high. This shows that families with the older adult still need an increase in knowledge about the care of psychotic functions, and an increase in knowledge will also have an impact on improving attitudes and skills in caring for the older adult by family members. This research can be a reference to determine the form of activities that support the improvement of psychosocial functions of the older adult .